¿QUÉ SIGNIFICA RAZÓN SITUADA? - de la Huerta, Marcos García (Revista de Filosofía (00348236), 2023)
Various meanings or levels of situated reason are distinguished: "Situated reason" [SR] presupposes a logos or reason, which is given in a particular historical and cultural sphere, i.e. it is conceived as temporal and worldly. The corresponding method is hermeneutic or interpretative, concerning the understanding of singularities. It is in the sphere of language and communication where it is proper to speak of reason or logos, which also mean word. SR It is associated with plurality, secularization and historicism; it is alien to monism in its various expressions: monotheism, monolinguals, monarchy, etc. It is a kind of post metaphysical rationality, distinct and alien to absolute knowledge. It means a decline (end?) of the primacy of the subject and of theory: situated reason entails a crisis of logo-centrism and a decentralization of truth.